1995
DOI: 10.1002/ls.3010070204
|View full text |Cite
|
Sign up to set email alerts
|

Visualisation of fuel‐lubricant interaction on the cylinder surface in the combustion chamber of SI engines

Abstract: Visualisation of fuel component penetration and release into the lubricating oil layer covering the combustion chamber wall has been achieved, using a laser‐induced fluorescence (LIF) test technique. Experimental data show that fuel component penetration into the oil layer contributes not only to unburnt hydrocarbon emissions in spark ignition (SI) engines, but also to engine oil degradation. Fuel components accumulated in the oil layer are transferred to the bulk in ring belt zones, after a measurable residen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Peralta (MIT) [14] found fuel dilution levels of 1-4% (by mass) in a fully warmed up Saturn four-cylinder gasoline engine. Similarly, Kovacs et al [15] found typical fuel dilution rates of 1.2% in a fully warmed up single cylinder 398 cm 3 displacement Kohler engine. Frottier et al (PSA/Peugeot/Citroen) [16] also found fuel dilution levels of 1.35% (by mass) in a Saturn engine after an 18-h long test.…”
Section: Fuel Dilution Levels In Vehiclesmentioning
confidence: 76%
“…Peralta (MIT) [14] found fuel dilution levels of 1-4% (by mass) in a fully warmed up Saturn four-cylinder gasoline engine. Similarly, Kovacs et al [15] found typical fuel dilution rates of 1.2% in a fully warmed up single cylinder 398 cm 3 displacement Kohler engine. Frottier et al (PSA/Peugeot/Citroen) [16] also found fuel dilution levels of 1.35% (by mass) in a Saturn engine after an 18-h long test.…”
Section: Fuel Dilution Levels In Vehiclesmentioning
confidence: 76%
“…Peralta (MIT) [14] found fuel dilution levels of 1 to 4% (by mass) in a fully warmed up Saturn four-cylinder gasoline engine. Similarly, Kovacs et al [15] found typical fuel dilution rates of 1.2% in a fully warmed up single cylinder 398 cm 3 displacement Kohler engine. Frottier et al (PSA/Peugeot/Citroen) [16] also found fuel dilution levels of 1.35% (by mass) in a Saturn engine after an 18-hour long test.…”
Section: Fuel Dilution Levels In Vehiclesmentioning
confidence: 76%
“…Laser-induced fluorescence, a technique based on the photoexcitation of a fluorophore or a fluorescent dye, has been extensively used as a general-purpose display tool in one-, two-, and three-dimensional applications. 1,2 However, it is used mainly as a tracer for qualitative purposes [3][4][5] and has seen only limited use as a quantitative tool. This limitation stems primarily from the fact that fluorescent intensity is dependent on the intensity of the exciting light.…”
Section: Introductionmentioning
confidence: 99%